Pelatihan dan Pendampingan Branding Modern dalam Peningkatan Kualitas Produk UMKM: Program Pengabdian kepada Masyarakat - Sarasati, Fajar; Wiharso, Gani; Prasetyo, Johan Hendri (Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This community service program was conducted to address challenges faced by micro, small, and medium enterprises (MSMEs) under the Genggam Teman Indonesia Foundation, particularly in product quality, branding, and technology use. Held in a hybrid format at Nusa Mandiri University, Jatiwaringin Campus, the program involved 21 MSME participants. The training aimed to strengthen knowledge and skills in branding, product design, raw material selection, production standards, and quality control. Methods included preliminary surveys, lectures, interactive discussions, and evaluations through pre- and post-training questionnaires. Results indicated improvements in participants’ understanding of product design and branding, ability to select quality raw materials, application of production standards, and implementation of quality control. Confidence in marketing products also increased. Active involvement of participants, who presented their products as case studies, made the sessions more contextual and practical. However, limited capital, restricted distribution channels, and varying digital literacy remained obstacles. In conclusion, the program enhanced MSMEs’ capacity in product quality and branding. Future activities should emphasize sustainable mentoring and collaboration with stakeholders to expand access to financing, distribution, and raw materials, thereby creating a stronger support system for MSME growth.